2016
DOI: 10.1111/jns.12160
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked Charcot‐Marie‐Tooth disease type 6 (CMTX6) patients with a p.R158H mutation in the pyruvate dehydrogenase kinase isoenzyme 3 gene

Abstract: Charcot-Marie-Tooth disease (CMT) is the most common inherited peripheral neuropathy. Mutations in the pyruvate dehydrogenase kinase isoenzyme 3 (PDK3) gene have been found to cause X-linked dominant CMT type 6 (CMTX6). This study identified the p.R158H PDK3 mutation after screening 67 probable X-linked CMT families. The mutation fully segregated with the phenotype, and genotyping the family indicated the mutation arose on a different haplotype compared with the original Australian CMTX6 family. Results of bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…Our laboratory identified a missense mutation (c.G473A p.R158H) in the pyruvate dehydrogenase kinase 3 (PDK3) gene causing an X-linked form of CMT, designated as CMTX6 3 . The same genetic mutation has been found in a second unrelated family, suggesting the specific nucleotide transition may be a hotspot for the R158H mutation 4 .…”
Section: Charcot-marie-tooth (Cmt) Is a Group Of Inherited Diseases Csupporting
confidence: 58%
See 1 more Smart Citation
“…Our laboratory identified a missense mutation (c.G473A p.R158H) in the pyruvate dehydrogenase kinase 3 (PDK3) gene causing an X-linked form of CMT, designated as CMTX6 3 . The same genetic mutation has been found in a second unrelated family, suggesting the specific nucleotide transition may be a hotspot for the R158H mutation 4 .…”
Section: Charcot-marie-tooth (Cmt) Is a Group Of Inherited Diseases Csupporting
confidence: 58%
“…Our previous investigation using patient fibroblasts from the family initially describing the CMTX6 mutation, showed that increased kinase activity of the mutant PDK3 3 led to hyperphosphorylation of the E1 subunit of the PDC and consequently attenuation of the complex activity 6 . The report of a second unrelated family with the same genetic mutation, demonstrated the p.R158H as a mutational "hotspot" in the PDK3 gene 4 . Experiments presented in this study showing E1 hyperphosphorylation in the two unrelated patient-derived fibroblast lines has provided compelling evidence confirming this as a CMTX6 phenotypic signature (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…The latter study's authors concluded that the finding "differs from demyelinating CMT1A patients and is similar to axonal CMT2A patients" [24]. Autosomal dominant distal neuromuscular disease research on HSPB8 mutations as the causal factor that resulted in myofibrillar aggregates and rimmed vacuolar myopathy combined with neurogenic changes revealed by MRI that the lower limb diffuse tissue alterations in the early disease stages eventually progressed in later stages to myopathy with a typical fatty deposition [45].…”
Section: Musculoskeletalmentioning
confidence: 99%
“…Having performed subsequent research on transgenic mice, these authors concluded that there might be an implication by their data findings that "overexpression of wild type as well as mutant PMP2 also causes the CMT1 phenotype, which has been documented in the PMP22" [23]. Kennerson et al studied 67 families for whom there already had been a probable suspicion of X-linked CMT [24]. In the latter study, the researchers found clinically, electrophysiologically, and via neuroimagery, that "the p.R158H PDK3 mutation [findings from a second CMTX6 family] were similar to the axonal neuropathy reported in the [original] Australian family," even though the phenotype and genotype results indicated that the two families had mutations of a different haplotype [24].…”
mentioning
confidence: 99%
See 1 more Smart Citation